(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background. Diabetic retinopathy (DR) is a vascular complication of diabetes, leading to vision loss and blindness in people of any age. This highlights the need for monitoring and predicting the course of DR to start early timely treatment and to prevent progression to the proliferative stages of the disease. Purpose. To study the features of ocular hemodynamics and develop the progression risk index for DR. Material and Methods. One hundred and sixty-five patients with non-proliferative diabetic retinopathy (NPDR) were randomly allocated to receive traditional treatment (control group), daily tablets of Tanakan (TT group), or daily endonasal electrophoresis of Tanakan (TE group) within ten days. The stages of DR were determined using the severity scale of the Early Treatment Diabetic Retinopathy Study (ETDRS). The main outcome measures were changes in DR severity (DRS), Doppler ultrasound imaging at months 1, 3, and 6. Results. Moderate negative correlations were found between peak systolic velocity (PSV) of the central retinal artery (CRA) and DRS, end-diastolic velocity (EDV) of CRA and DRS, PSV of central retinal vein (CRV) and DRS, PSV of the short posterior ciliary artery (SPCA) and DRS. Developed diabetic retinopathy progression risk index (DRPRI) was less than 1,0 in the TE group that enabled us to predict DR stability or improvement. Conclusions. This validation study demonstrated that PSV and DRS are correlated, and PSV can be used to diagnose the stages of DR. Developed DRPRI can be used to assess the effectiveness of treatment and to predict DR, which is essential for determining further patient management tactics.